Advances in service-oriented and cloud computing : workshops of ESOCC 2015, Taormina, Italy, September 15-17, 2015, revised selected papers /: workshops of ESOCC 2015, Taormina, Italy, September 15-17, 2015, revised selected papers. (2016) - Unknown
No abstract available